Kas'rat of Umluj folklore | كسرات من تراث أملج الشعبي - Al-Darini | الدريني, Anas | أنس (Reality Channel | قناة الواقع, 2023)
The city of Umluj is characterized by beaches and islands along its coasts, and it is one of the governorates of the Tabuk region overlooking the Red Sea in the Kingdom of Saudi Arabia. In the waters of its clear sea, in addition to its distinction of being a green oasis, palm trees are spread on its coasts, and on the other hand, the Umluj governorate includes many heritage sites that express the civilization and splendor of the place. | تتميز مدينة أملج بالشواطئ والجزر الممتدة على طول سواحلها، وهي إحدى محافظات منطقة تبوك المطلة على البحر الأحمر في المملكة العربية السعودية، كما تُعتبر من المدن الساحلية الغنية بالأحياء البحرية والشعاب المرجانية، وهي مقصد لكثير من السيّاح من كافة أنحاء المملكة العربية السعودية لممارسة الهوايات البحرية بأنواعها في مياه بحرها الصافي، بالإضافة إلى تميزها بكونها واحة خضراء ينتشر النخيل على سواحلها، ومن جانب آخر فإنَّ محافظة أملج تضم الكثير من المواقع التراثية التي تعبر عن حضارة المكان وروعته.